Forms of Spelling Errors in Biography Texts of Grade X Students of SMA Negeri 1 Pancung Soal - Amelia Wulandari; Aura Afriananda; Della Akmalia; Klaraysa Zeta Lorenza; Afnita (Raja Zulkarnain Education Foundation, 2026)
Writing in Indonesian has been taught from elementary school to high school. Spelling is one of the learning objectives, but many spelling errors are still found among high school students. This study aims to analyze spelling errors in biographical texts of 10th-grade students at SMA Negeri 1 Pancung Soal. This study used a qualitative descriptive method. The research data, in the form of biographical texts written by fourteen 10th-grade students, were collected using library techniques. The data on spelling errors were analyzed qualitatively by identifying, classifying, and describing the types of spelling errors. The results showed that the most dominant spelling errors made by students were capitalization errors (38%), followed by punctuation errors (27%), compound word errors (21%), and loanword errors (14%). Spelling errors are caused by students' lack of understanding of Indonesian spelling rules and language habits that do not conform to standard rules. The results of this study are expected to be used as considerations for Indonesian language teachers in improving learning strategies for writing biographical texts with an emphasis on correct spelling.